Variations in the Physico-chemical Parameters of Some N-Methyl Substituted Barbiturate Derivatives - RAY, RAKESH; SHARMA, J.D.; LIMAYE, S.N. (Asian Journal of Chemistry, 2010)
The relative activity for the series of substituted barbituric acid derivatives show highly dependent lipophilic character. The increasing lipophilic character facilitate the movement of drug through lipophilic biophases and direct it on the sites of action.